Anísio Teixeira: apontamentos sobre democratização e qualidade do ensino - Carbello, Sandra Regina Cassol; Ribeiro, Ricardo [UNESP] (Universidade Estadual de Maringa, 2014)
Anísio Teixeira: notes on democratization and quality of education. The work of Anísio Teixeira is the support of this study in a discussion of the democratization process in Brazilian education. We raised elements to contrast the idea of access democratization as a trigger to the process of decrease in quality of the public education offered in the country. The discussion initially presented the journey of this renowned Brazilian educator. Subsequently, we presented data on the early 20th century public education, period when he leads important positions in public education. We conclude the study by presenting the “School-park” proposed as he idealized the organization of elementary school.

Este texto retoma a obra de Anísio Teixeira para discutir o processo de democratização da educação brasileira. Buscamos elementos para contrapor a ideia de que a democratização do acesso desencadeou o processo de diminuição da qualidade da educação pública ofertada no país. Para esta discussão, inicialmente apresentamos a trajetória deste renomado educador brasileiro. Na sequência, apresentamos os dados sobre a educação pública do início do século XX, período em que ele assume cargos importantes na educação pública. Finalizamos o texto apresentando a Escola-Parque, proposta, por ele idealizada, para organizar o ensino elementar.
Anísio Teixeira: notes on democratization and quality of education
Keywords: Public education; Quality of education; Democratization; Educação pública; Qualidade de ensino; Democratização